Preoperative embolization of hypervascular spinal tumors: Two case reports - Binh, Nguyen Thai; Hoa, Tran Quoc; Linh, Le Tuan; My, Thieu-Thi Tra; Anh, Pham Quynh; Duc, Nguyen Minh (Journal of Clinical Imaging Science)
The performance of preoperative embolization on a spinal tumor can be a useful adjunctive procedure that minimizes blood loss and complications, particularly for both metastatic and non-metastatic hypervascular tumors. We discuss two cases of hypervascular spinal tumors that were successfully treated with preoperative embolization and surgery. The first patient was an 18-year-old man who presented with cervical and shoulder pain for two months without paralysis or weakness. Magnetic resonance imaging revealed a tumor located in the D2 posterior vertebral arch that extended into the spinal canal and compressed the spinal cord. The second patient was a 68-year-old man with back pain that radiated to the legs for ten days. Magnetic resonance imaging revealed a mass in the L4 vertebral body. Both patients received tumor embolization and surgery. After surgery, neither patient experienced any major complications. Histological examination revealed osteoblastoma in the first patient and plasmacytoma in the second patient.